Social norms and the feeling of justice about unequal family practices - Gabrielle Poeschl (2008)
After briefly retracing the origins of the present day unbalanced division of family work, this paper article summarizes results from three studies conducted with married adults and unmarried young adults from northern Portugal. The data support the idea that (a) unequal family practices do not change because traditional practices are social norms that orientate individuals' behavior; (b) individuals do not comply passively to these social norms but consider that the normative practices are fair; (c) normative family practices are considered to be fair because women, as well as men, seem to gain benefits from traditional family organization. The social consequences for women of the maintenance of normative family practices are discussed.